Religion and politics in international relations: the modern myth - Fitzgerald, Timothy (Continuum, 2011)
Introduction A : focusing the problem -- Introduction B : contextualizing the problem in the author's research background -- Christopher Hitchens and how religion poisons everything -- Eli Berman, religious terrorism, and the innocent economist -- International relations and religion's return from exile -- Scott M. Thomas, religion resurging, and international relations -- Elizabeth Shakman Hurd : the politics of secularism in international relations -- Where the author stands : a question of commitment